Physical and Chemical Characteristics of Biscuits with Catfish Flour (Clarias batrachus) Addition - Rini Umiyati; Putri Fara Dila; Dani Satrio Wicaksono; M Khoiron Ferdiansyah; Rizky Muliani Dwi Ujianti (Universitas PGRI Semarang, 2023)
Fish flour is an important source of animal protein because it contains complex amino acids such as lysine and metinine which are found in animal and fish feeds. Biscuits are snacks that are easy to get and are liked by many people. The purpose of this study was to determine the effect of different characteristics of catfish flour biscuits with the addition of each concentration treatment on the physical, chemical and organoleptic properties of catfish biscuits (0%, 5%, 10%, 15%). The research method used a Completely Randomized Design of One Component Factors with four treatments B0, B1, B2 and B3. Research analysis carried out included chemical properties (moisture content, ash content, protein content, fat content) and color test. The results of this study indicate that biscuits with the addition of catfish flour obtained a moisture content between 4.96-4.53%, ash content 2.19-4.07%, fat content 62.95-78.23%, protein content 6.74 -8.68%, Color between 10.73-7.73%, Texture between 24.01-23.18%. The color test results with the addition of catfish flour can reduce the value of the color test.